Two-phase spray cooling with HFC-134a and HFO-1234yf on practical enhanced surfaces. (25th February 2018) - Bostanci, H.; Altalidi, S.S.; Nasrazadani, S.
Highlights: A spray cooling study was performed with HFC-134a and HFO-1234yf refrigerants. Smooth, electroplated microporous (EMS), sanded, and blasted surfaces were tested. Up to 370 W/cm 2 heat flux and 80 kW/m 2  °C heat transfer coefficient were obtained. HFC-134a offered better cooling performance than HFO-1234yf mainly due to properties. Surface EMS achieved enhancement by promoting boiling through surface nucleation. Abstract: An experimental study was conducted to characterize the spray cooling performance of HFC-134a and HFO-1234yf refrigerants using enhanced surfaces produced by simple processes with implications for active two-phase cooling of automotive power electronics. Experimental setup involved a closed loop spray cooling system featuring a pressure atomized spray nozzle and a 1-cm 2 heater sample that simulated a high heat flux device. Heat transfer surfaces consisted of three modified surfaces, namely, electroplated-microporous, sanded, and blasted surfaces, along with a smooth surface that served as a reference. Tests were performed with saturated working fluids at room temperature (22 °C) using a range of liquid flow rates (2.5–4.5 ml/cm 2  s). Based on the results, HFC-134a provided a better performance through higher heat transfer coefficient (HTC) and critical heat flux (CHF) values compared to HFO-1234yf that can mainly be attributed to the thermophysical properties and their effect on two-phase heat transfer process. The electroplated-microporous surface achieved the highest heat transfer enhancement among the tested surfaces. Overall, this study provided a framework for two-phase spray cooling performance of the current and next-generation refrigerants aimed for advanced thermal management of automotive power inverter modules towards achieving cost, size and weight reduction.